Insecure in love : how anxious attachment can make you feel jealous, needy, and worried and what you can do about it - Becker-Phelps, Leslie (New York ; London, UK : Norton, 2010)
Almost everyone has felt jealous or insecure in a romantic relationship at some point in their lives. But people who constantly feel these emotions may suffer from anxious attachment, a fear of abandonment often rooted in early childhood experiences. In Insecure in Love, readers will learn how to overcome attachment anxiety using compassionate self-awareness, a technique that can help them recognize negative thoughts and get to the root of their insecurities so that they can cultivate secure, healthy relationships to last a lifetime.
Contents note continued: It Takes Work to Tango -- 10.Working It Out -- Asking for Support -- Talking Through Conflicts -- The Gift of Forgiveness -- Moving On -- Closing Thoughts.
Includes bibliographical references.
Keywords: Love; Man-woman relationships; Self-consciousness (Awareness); Anxiety